The potential of honey from Apis cerana in preventing chronic inflammation by downregulating the NF-?B pathway - Hadi, Samsul; Setiawan, Deni; Sukmana, M. Laily Qadry; Nastiti, Kunti (Journal of Midwifery and Nursing, 2024)
Chronic inflammation is an inflammatory condition that persists over a long period of time causing tissue damage and contributing to the development of chronic diseases such as arthritis, heart disease, or certain autoimmune conditions. The protein that plays a role in this regulation is the up-regulation of NF-?B, this is the aim of this research, namely to determine the potential of the compounds contained in A.cerana honey to bind with NF-?B. The research stages carried out were preparing the NF-?B protein structure database, protein preparation using the Yasara application, structure preparation and optimization using the Chemaxon application, as well as validating the molecular docking method and docking of compounds from A.cerana honey on the NF-?B protein using the PLANT application. The research results show that Ellagic acid, Taxifolin, Quercetin and Chrysin have affinity and form hydrogen bonds with the NF-?B protein. The binding energy between Ellagic acid, Taxifolin, Quercetin and Chrysin with the NF-?B protein respectively is 78,822; -64.89; -64,872 and -64,935. Ellagic acid, Taxifolin, Quercetin and Chrysin have potential anti-inflammatory activity through binding to the NF-?B protein, thereby preventing the inflammatory process.